Cost-effectiveness of treating normal tension glaucoma - Li, Emmy Y; Tham, Clement C; Chi, Stanley C; Lam, Dennis S (Investigative ophthalmology & visual science, 2013)
To assess the long-term cost-effectiveness of treating normal tension glaucoma (NTG). A Markov decision-analytic health model was developed to determine the cost-effectiveness of treating NTG with IOP lowering therapy to prevent progressive visual field loss. Transitional probabilities were derived from the Collaborative Normal Tension Glaucoma Study and cost data obtained from the literature and the Medicare fee schedule. Incremental cost-effectiveness ratios (ICER) of treating all patients with NTG and treating selected individuals with risk factors for disease progression were determined using Monte Carlo simulation. Sensitivity analyses were performed by varying the cost of consultations, medications, laser/surgery, and adjusting utility loss from progressed states. The ICER of treating all patients with NTG over a 10-year period was United States (US) $34,225 per quality-adjusted life year (QALY). The ICER would be reduced when treatment was offered selectively to those with risk factors for disease progression. The ICER for treating NTG patients with disc hemorrhage, migraine, and those who were female were US $24,350, US $25,533, and US $27,000 per QALY, respectively. The cost-effectiveness of treating all NTG patients in this model was sensitive to cost fluctuation of medications, choice of utility score associated with disease progression, and insensitive to cost of consultations and laser/surgery. It is cost-effective, in the long-term, to offer IOP lowering therapy, aiming for a 30% reduction from the baseline, to all NTG patients. The incremental cost-effectiveness ratio of treating all patients with normal tension glaucoma over a 10-year period was $34,225 per quality-adjusted life year and should be offered to individuals in need.